2020
DOI: 10.1016/j.scitotenv.2020.140825
|View full text |Cite
|
Sign up to set email alerts
|

Improving VOCs control strategies based on source characteristics and chemical reactivity in a typical coastal city of South China through measurement and emission inventory

Abstract: In China, the corresponding control directives for volatile organic compounds (VOCs) have been based on primary emissions, rarely considering reactive speciation. To seek more effective VOCs control strategies, we investigated 107 VOC species in a typical coastal city (Beihai) of South China, from August to November 2018. Meanwhile, a high-resolution anthropogenic VOCs monthly emission inventory (EI) was established for 2018. For source apportionments (SAs) reliability, comparisons of source structures derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(12 citation statements)
references
References 50 publications
2
9
1
Order By: Relevance
“…In previous years (2016–2019), the significant positive correlation with NO 2 in daily resolution, instead of negative correlations in hourly, showed that increased O 3 concentrations are highly associated with increased daily emissions of O 3 precursors. During the lockdown period in 2020, O 3 showed a strong positive correlation with NO 2 in daily resolution (r s = 0.375, p < 0.01), and a moderate positive correlation in hourly resolution (r s = 0.106, p < 0.05), indicating, unlike previous studies ( Fu et al, 2020 ), that O 3 concentrations were more likely to depend on NOx concentrations. Besides variabilities in its precursors, as a secondary photochemical pollutant, fluctuations in O 3 concentrations can also be driven by changes in meteorological conditions, which will be detailed below.…”
Section: Resultscontrasting
confidence: 71%
See 2 more Smart Citations
“…In previous years (2016–2019), the significant positive correlation with NO 2 in daily resolution, instead of negative correlations in hourly, showed that increased O 3 concentrations are highly associated with increased daily emissions of O 3 precursors. During the lockdown period in 2020, O 3 showed a strong positive correlation with NO 2 in daily resolution (r s = 0.375, p < 0.01), and a moderate positive correlation in hourly resolution (r s = 0.106, p < 0.05), indicating, unlike previous studies ( Fu et al, 2020 ), that O 3 concentrations were more likely to depend on NOx concentrations. Besides variabilities in its precursors, as a secondary photochemical pollutant, fluctuations in O 3 concentrations can also be driven by changes in meteorological conditions, which will be detailed below.…”
Section: Resultscontrasting
confidence: 71%
“…In particular, Beihai was most frequently affected by onshore air masses (Clusters 1 and 2, 58%), followed by Chongzuo (Clusters 1 and 3, 45%), Yulin (Clusters 1 and 3, 31%) and Nanning (Cluster 3, 24%). In view of the clean air from the South China Sea ( Fu et al, 2020 ) and lower O 3 concentrations in Southern Guangxi cities ( Fig. S1 ), we could conclude that the regional transport of air masses facilitated the overall decline in O 3 in Southern Guangxi.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…As shown in Fig. 7, their contributions to the total OFP are different in different areas (Duan et al, 2008;Deng et al, 2019;Fu et al, 2020;Zhao et al, 2020;Zhou et al, 2020;Zhu et al, 2020). Contributions of the top eight NMVOCs to OFP account for 51%−69% of the total, among which OVOCs, especially formaldehyde and acetaldehyde, contribute more to OFP in megacities.…”
Section: Key Photochemical Activitymentioning
confidence: 99%
“…Therefore, studying the emission characteristics and atmospheric chemical activity of anthropogenic VOCs emission source is an important basis for understanding the formation mechanism of air pollution and devising effective control policies (Li et al, 2020). In addition, source profiles especially the localized are important for source apportionment, which could provide data in support of air quality model simulation and air pollution control strategies (Song et al, 2008;Fu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%